The Role of CD4+CD8+ T Cells in HIV Infection With Tuberculosis - Shi Zou; Shi Zou; Yuting Tan; Yuting Tan; Yanni Xiang; Yang Liu; Yang Liu; Qi Zhu; Songjie Wu; Songjie Wu; Wei Guo; Wei Guo; et al. (Frontiers Media S.A., 2022)
BackgroundTuberculosis (TB) is an important opportunistic infection in acquired immunodeficiency diseases (AIDS). Although the frequency of CD4+CD8+ double-positive (DP) T cells has been observed to increase in pathological conditions, their role (phenotypic and functional) is poorly described, especially in human immunodeficiency virus (HIV) infection with TB (HIV/TB (HT) coinfection).MethodsThe percentage and phenotypic and functional properties of peripheral blood DP T cells in patients with HT coinfection in comparison to uninfected controls and to patients with HIV or TB mono-infection were analyzed by direct intracellular cytokine staining (ICS).ResultsTotal and CD4lowCD8high DP T cells were significantly increased in patients with both HIV and TB mono-infection, especially in patients with HT coinfection. Compared with healthy controls (HCs), the percentage of DP T cells expressing chemokine receptor 5 (CCR5) in patients with HT coinfection was significantly higher. Compared with HCs and patients with TB, a lower percentage of tumor necrosis factor α (TNF-α) secreting DP T cells and a higher percentage of granzyme A-secreting DP T cells were observed in patients with HIV mono-infection and HT coinfection, respectively. In addition, DP T cells expressed more cytolytic markers (granzyme A and perforin) than CD4+ T cells, but similarly to CD8+ T cells in patients with HT coinfection.ConclusionsOur data suggested that HT coinfection resulted in a marked increase in DP T cells, especially the CD4lowCD8high subpopulation. DP T cells may be susceptible to HT coinfection, and have the same cytotoxic function as CD8+ T cells.